Aging and the politics of monetary policy in Japan. (28th December 2022) - Yamada, Kyohei; Park, Gene
Abstract: This paper explores how Japan's aging population impacts the politics of monetary policy. Previous research suggests that the elderly have a variety of distinct policy preferences. Given that elderly voters also have higher voting rates, the rapid greying of the population could have significant effects on distributive struggles over economic policy across much of the developed world. In Japan, aging is advancing rapidly, and the central bank has engaged in massive monetary stimulus to induce inflation, which existing work suggests the elderly should oppose. Analyzing results from three surveys, this paper has three central findings: (1) the elderly tend to have higher inflation aversion, (2) the elderly display some opposition to quantitative easing (QE), and (3) despite such policy preferences, the concentration of elderly in electoral districts has no significant effect on the preferences either of legislative incumbents or candidates. The third finding is attributable to the fact that elderly opposition to QE is moderated by their partisan identification. Elderly Liberal Democratic Party (LDP) voters have systematically lower opposition to QE, likely reflecting that these voters have aligned their preferences with the LDP's policies.